High-Energy Transsyndesmotic Ankle Fracture Dislocation: A Case Report and Systematic Literature Review - Yinshuan Deng; Chenhui Dong; Xiaojie Yang; Rui Liu; Feiyi Hou; Shensong Li; Kanglai Tang (Case Reports in Orthopedics, 2018)
High-energy trauma can cause transsyndesmotic ankle fracture dislocation. These fractures are quite rare. Here we present a clinical case of a male patient with this type of injury. A systematic review of PubMed, Ovid MEDLINE, and Embase electronic databases revealed only two prior publications on a similar topic. We discuss the typical clinical features of these injuries, the treatment of high-energy trauma which can cause transsyndesmotic ankle fracture dislocation, and its prognosis.